The Biblical Dimension of Religious Instruction in Poland - Zając, Marian (Verbum vitae, 2021)
The article concerns the issue of religious instruction in Polish state schools, especially its inspiration from the Bible as the primary source of the transmission of faith. When religious education classes were introduced in schools, a confessional model of their performance was adopted, thus leading to establishing closer ties with churches and religious associations as well as developing personal faith. The methodology of my research was based on analysing the current anchoring of the teaching of religion in the Polish state law and the guidelines of the Catholic Church. Next, the 2018 Core Curriculum for the Catechesis of the Catholic Church in Poland, related to the reform of the Polish education system and the completely new situation resulting from the liquidation of the junior high school stage of education, was used to show biblical guidelines for religious instruction and a set of methodological tools that guarantee its effectiveness. Confessional religion classes are currently organized in all government-run schools in Poland, and according to recent statistical data they significantly contribute to their better functioning. Consequently, there is a need to appeal for the continuation of religious education in schools and its modification based on multimedia technology, and there is a necessity to overcome the tendency to remove classes of religion from Polish public schools.